Some cone separation results and applications - Durea, M. (Rev. Anal. Numér. Théor. Approx., 2008)
In this note we present some cone separation results in infinite dimensional spaces. Our approach is mainly based on two different types of cone outer approximation. Then we consider an application to vector optimization.